Assessing geometric microliths as cultural markers through an analysis of shape variation and projectile performance - Alfredo Cortell-Nicolau; Alastair Key; Antoni Palomo (Scientific Reports)
Abstract European geometric microlith shape variation is often used as a marker of cultural differences between groups of Mesolithic hunter gatherers and/or Neolithic farmers. Indeed, the 2D plan-view shape of these lithics is known to vary in spatially and temporally systematic ways between archaeological sites. Such differences are well evidenced in the Iberian Peninsula between the 9th and 8th millennia BP. Here we test an alternative hypothesis for the structured variation observed in geometric microliths: whether their plan-view shape significantly impacts the force, energy and displacement experienced when they are used as projectile tips. If functional differences between groups help to explain the shape variation observed in the archaeological record, then any role for cultural (non-functional social) explanations is potentially reduced. We undertook controlled static penetration tests using an Instron materials tester and an assemblage of replicated Iberian geometric microliths hafted to standardised wooden shafts. Results indicate that the maximum force required, energy used, and displacement at maximum force experienced by these hafted geometric microliths when used as projectile armatures is not significantly influenced by their 2D plan-view shape. Rather, gross form attributes such as maximum thickness, distance from the tip of the microlith to the start of the shaft, and the maximum width of the hafting substrate/adhesive are the greatest determinants of penetration ease, along with the positioning of the microlith when hafted. Our data therefore supports past research that proposes a cultural role for geometric microlithic shape variation in the European Mesolithic and Early Neolithic. Moreover, it highlights the functional importance of maintaining relatively thin microblades during microlith production, along with taking care to minimise the size of hafting components and the necessity to haft them in the most efficient way.